Meningkatkan Kesadaran dan Dorongan Yang Kuat Untuk Menguasai Pengetahuan dan Ketrampilan Yang Menjadi Program Sekolah Dengan Model Pembelajaran Learning Community Siswa Kelas VIII-A SMP Negeri 1 Sawahan Kabupaten Madiun Tahun Pelajaran 2017/2018 - Pit Wahyuni (EQUILIBRIUM : Jurnal Ilmiah Ekonomi dan Pembelajarannya, 2021)
This study aims to determine the application of the Learning Community model to improve the strong motivation of class VIII-A students of SMP Negeri 1 Sawahan, Madiun Regency. This model is a method that is very suitable for the material used to increase the knowledge and skills of school programs. The research method in this study is a Classroom Action Research (PTK). The results of the study seem to provide changes in action in cycles I, II, and III. 1) Efforts to increase awareness and strong encouragement to master the knowledge and skills that become school programs so that students participate in the learning process in class VIII-A of SMP Negeri 1 Sawahan, Madiun Regency in the 2017/2018 Academic Year through providing modules / dictates to improve initial abilities (entry behavior) of students and revising the misconceptions of awareness and a strong urge to master the knowledge and skills that became the school program in cycle II, which might cause obstacles to developing students' understanding of the concept of awareness and a strong urge to master knowledge and skills which is a school program to be studied, then the application of the learning community model through group study together or helping each other in lessons, 2) Learning Community learning model is able to improve student learning outcomes both in terms of student response aspects, teacher success student and teacher reactions, as well as environmental conditions. This learning model is also able to create a learning atmosphere that is able to increase awareness and encourage students to master the abilities and skills of students in the classroom.